Synthesis of the Se-HPCF composite via a liquid-solution route and its stable cycling performance in Li–Se batteries. Issue 41 (13th October 2020) - Chen, Xi; Xu, Lihong; Zeng, Lingxing; Wang, Yiyi; Zeng, Shihan; Li, Hongzhou; Li, Xinye; Qian, Qingrong; Wei, Mingdeng; Chen, Qinghua
Abstract : The Se-HPCF composite was fabricated via a liquid-solution route followed by calcination treatment, and was used as a high-rate anode material for Li–Se batteries. Abstract : In pursuit of a one-dimensional (1D) porous carbon framework to restrain selenium for advanced lithium–selenium batteries, the Se-hierarchical porous carbon fiber composite (Se-HPCF) is synthesized via a liquid-solution route followed by calcination treatment. The unique architecture of the HPCF, which exhibits a large surface area and high pore volume, is fabricated using sodium lignosulfonate (LN) as a green pore-forming agent via electrospinning. As a cathode material for Li–Se batteries, the Se-HPCF composite exhibits superior electrochemical performance. A reversible capacity of 533 mA h g −1 is maintained at a rate of 0.2C after 50 cycles. In addition, the Se-HPCF composite delivers high rate performance with a high specific capacity of 351 mA h g −1 at 5C. The enhanced capacity retention and rate performance of Se-HPCF is generated by the 1D structure characteristics, and the liquid phase melting diffusion method could be applied to produce other related materials.